Systemic Risk in Global Volatility Spillover Networks: Evidence from Option-implied Volatility Indices - Zihui Yang; Yinggang Zhou (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
With option-implied volatility indices, we provide a new tool for event studies in a network setting and document systemic risk in the spillover networks across global financial markets. Network linkages are sufficiently asymmetric because the US stock and bond markets play as dominant volatility suppliers to other countries and markets. Shocks from the US generate systemic risk through intensifying volatility spillovers across countries and asset classes. The findings offer new evidence that asymmetric network linkages can lead to sizable aggregate fluctuations and thus potential systemic risk.
Keywords: C00; 330; Network; Option-implied Volatility; Spillover; Asymmetric linkage; Systemic risk